Creating Women Characters in Horror Films using AI: Avoiding Male Gaze Characters Template - Sofiyanti, Devina; Irwanto, Irwanto (Universitas Multimedia Nusantara, 2024)
In screenwriting, one of the most essential elements is character. Characters are usually shaped by three critical factors: physical appearance, psychology, and sociology. In horror films, female characters are often used as protagonists, but in the history of horror films, female characters are trapped by the male gaze. The male gaze functions as a mechanism to dehumanize and commodify women, viewing them solely through the lens of heterosexual male desire. Laura Mulvey, in her seminal 1975 essay